2015
DOI: 10.1007/s00423-015-1349-0
|View full text |Cite
|
Sign up to set email alerts
|

Totally laparoscopic gastrectomy for gastric cancer after endoscopic submucosal dissection: a propensity score matching analysis

Abstract: Results: Operative times for TLG in ESD group and non-ESD group were 228.2 ± 53.9 and 228.1 ± 52.7 min (P=0.989), and blood loss was 45.7 ± 83.0, 71.3 ± 74.5 g, respectively (P=0.161). There were no significant differences between the groups of ESD and non-ESD in postoperative recovery and postoperative complications. In totally laparoscopic distal gastrectomy (TLDG), the patients with ESD-resected specimens of more than 50 mm in diameter had significantly longer operative times (P=0.009).Conclusions: In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several studies [14][15][16] support similar results but also point that adhesion may result in difficult surgery and greater blood loss, and intended operative procedure can be changed due to contraction of the ESD scar near pylorus or cardia. [13][14][15]17 As all we know, laparoscopic gastrectomy has become standard treatment for early gastric cancer. Laparoscopic gastrectomy with adequate lymph node dissection can be safely applied for patients with non-curative ESD regarding postoperative complications and oncologic outcomes.…”
Section: Editorialmentioning
confidence: 73%
See 1 more Smart Citation
“…Several studies [14][15][16] support similar results but also point that adhesion may result in difficult surgery and greater blood loss, and intended operative procedure can be changed due to contraction of the ESD scar near pylorus or cardia. [13][14][15]17 As all we know, laparoscopic gastrectomy has become standard treatment for early gastric cancer. Laparoscopic gastrectomy with adequate lymph node dissection can be safely applied for patients with non-curative ESD regarding postoperative complications and oncologic outcomes.…”
Section: Editorialmentioning
confidence: 73%
“…Laparoscopic gastrectomy with adequate lymph node dissection can be safely applied for patients with non-curative ESD regarding postoperative complications and oncologic outcomes. 14,16 Authors compared the early postoperative outcomes according to the interval between ESD and additional gastrectomy. No established principal exists regarding ideal timing of surgery after ESD.…”
Section: Editorialmentioning
confidence: 99%
“…ESD in EGC causes an artificial gastric ulceration, local inflammation, subsequent fibrosis, and even adhesions in the outer gastric wall, which has a negative intraprocedural impact on additional LG in patients who have undergone non-curative ESD[14]. Previous studies have demonstrated that ESD is not associated with postoperative complications during or after an additional LG in patients who underwent noncurative ESD[15-17]. Our study found that LG can achieve good short-term surgical outcomes for gastric cancer after noncurative ESD.…”
Section: Discussionmentioning
confidence: 99%
“…ESD-induced inflammation causes edema, fibrosis, and intraabdominal adhesions, which might increase the difficulties and the risk of complications during subsequent LG[3,14]. However, relatively few data are available on the influence of previous ESD on LG[15-17].…”
Section: Introductionmentioning
confidence: 99%